Dynamic behavior of jet-swirl spray under resonance condition with external excitation. (December 2021) - Jo, Hyeontaek; Jeong, Gijeong; Bae, Jinhyun; Yoon, Youngbin
Abstract: Gas-centered swirl coaxial (GCSC) injectors are used in many liquid propellant rocket engines to improve combustion efficiency. In this study, fluctuation of the mass flow rate is analyzed to investigate influence of external excitation in gas feed line on the mass flow rate distribution of sprays. Water and air are used as simulants for the liquid kerosene and gas oxygen, respectively. With external excitation (354 and 1062 Hz), atomization processes changes and periodic breakup phenomenon of a spray occurs. Liquid film thickness at the exit of the injector shows that the width of liquid mass flow rate wave is reserved when the instability mode changes. However, behavior of the liquid droplets captured with a structured laser illumination planar imaging (SLIPI) system for laser diagnostics indicates that time domain concentration of liquid mass becomes more severe with the second instability mode outside the injector. This study can provide a reference for liquid mass distribution with external excitation on gas and imply that resonance in injector feeding systems is one of the important factors in combustion instability. Highlights: Periodic breakup of spray from a jet swirl injector with external excitation was observed. Atomization process and sprays shapes change for acoustic resonance with external excitation. Instability accelerates atomization process and makes droplet location closer to injector. Mass flow rate fluctuation was more severe for 1062 Hz than for 354 Hz resonance frequency.